(untitled) (The Lumbini Journal of Business and Economics, 2025)
Purpose: This study aims to critically examine current SMA scholarship by identifying key themes, methodologies, and theoretical perspectives; to assess the impact of SMA practices on performance outcomes such as profitability, efficiency, and competitive advantage; and to identify gaps in the research while suggesting directions for future inquiry. Methods: The study employed a systematic literature review of recent empirical and conceptual works published between 2016 and 2025 utilizing JSTOR, Research for life, Dimensions and Google Scholar database. A mapping review with thematic synthesis approach was used to analyze similarities and differences across studies, focusing on strategic orientation, organizational outcomes, sustainability integration, and methodological approaches. Results: SMA adoption is strongly shaped by organizational strategies, managerial attitudes, and external competition. SMA contributes positively to financial outcomes, resource optimization, and long-term competitiveness, while also expanding its scope to include sustainability and stakeholder considerations. Conclusions: SMA is a multidimensional tool linking financial and non-financial performance measures with strategic decision-making. Its effective use depends not only on technical adoption but also on leadership, organizational culture, and alignment with business processes.